Cytotoxicity Study in Non Malignant Fibroblast L929 Cell Line with Mucuna pruriens Seed Extract - Acharya Bal Krishna; Hemanth Kumar Manikyam; Niti Sharma (International Journal of Phytomedicine, 2015)
Mucuna pruriens (L.) DC. (Leguminosae), commonly called velvet bean has been long used by tribes as an antidote for various snakebite, for treating depression and various nervous disorders, Parkinson’s disease, arthritis and also has potent anti-urolithiatic, anti- diabetic, anti-cancer, anti-oxidant activities. To evaluate the potential cytotoxicity of the hydroalcoholic extract of Mucuna pruriens seeds in non-malignant fibroblast L929 cell line. To access the toxic nature of the seeds, a hydroalcoholic extract was prepared and tested for its cytotoxic effects on non-malignant fibroblast L929 cell line at various concentrations (1.25 mg/ml, 2.5 mg/ml and 5 mg/ml). Viability (%), cell death (%), cytotoxicity grading, proliferation rate and growth inhibition values were calculated. No substantial difference in viability (%), cell death (%), growth inhibition (%) and proliferation rate were observed either at 24 h or 48 h following treatment with various concentrations of the extract as compared to the negative control. No toxicity was observed at any concentration of the extract, implying that the L-DOPA enriched extract of Mucuna pruriens is not toxic to the non malignant cells. These results confirmed that Mucuna pruriens seeds are safe and can be used as medicine for the treatment of various diseases.